Comparative Performance Analysis of Bitcoin, LQ45 Stocks, and Antam Gold as Investment Options - Zeze Zakaria Hamzah; Mujito; Herman; Wahid Akbar Basudani (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The advancement of technology and digitalization has broadened access to various investment instruments, driving greater participation in investment activities, especially among younger generations. This shift highlights a contrast between classical investment theory, which emphasizes rational decision-making, and real-world investor behavior often influenced by trends, emotions, and phenomena like fear of missing out. This study aims to compare the performance of Bitcoin, LQ45 index stocks, and Antam gold using recent data, including local gold prices. A comparative analysis approach is used to evaluate which investment yields the best performance. The findings, based on the Sharpe, Treynor, and Jensen methods, reveal notable performance differences. Bitcoin achieved the highest Sharpe ratio, reflecting high potential returns relative to total risk, making it attractive for high-risk-tolerant investors. Antam Gold ranked highest on the Treynor ratio, indicating its strength in generating returns relative to market risk (beta), and serving as a more stable option for conservative investors. LQ45 stocks excelled using the Jensen method, showing their ability to deliver returns above market expectations, ideal for fund managers seeking to outperform benchmarks. This research reinforces the importance of aligning investment instrument choices with individual risk profiles and financial goals.